Analisis Perbandingan Kinerja Keuangan Perusahaan Layanan Kesehatan Dan Perusahaan Jasa Transportasi Pada Masa Pandemi Covid 19 Di Indonesia - Muhammad Cholis; Darmanto Darmanto (ITB AAS Indonesia, 2025)
The company's financial performance is the result of the company's operating activities presented in the form of financial ratio numbers. In this study, the financial ratios used as proxies for financial performance are the current ratio, debt to asset ratio or liability to asset, net profit margin ratio, and working capital turnover ratio. The purpose of the study was to analyze the comparative financial performance of the health service and transportation service company groups during the Covid-19 pandemic using the independent sample t-test. This study also tested the comparative financial performance of the sample companies in the period before and during the Covid-19 pandemic as an additional test, using the paired sample t-test. The sample selection was carried out by purposive sampling, with the research sample being a group of health service and transportation service companies listed on the Indonesia Stock Exchange in the period 2018 to 2021. The results of the study were that the variables of the current ratio and liability to asset ratio of health service companies were significantly different from transportation service companies. Meanwhile, the net profit margin ratio and working capital turnover ratio did not differ significantly between health service companies and transportation service companies. In addition, the results also showed that although there was no significant difference between the periods before and during the pandemic, all research variables had an average figure that increased during the Covid-19 pandemic compared to before the Covid-19 pandemic.